Focus on PD-1/PD-L1-Targeting Antibodies in Colorectal Cancer: Are There Options Beyond Dostarlimab, Nivolumab, and Pembrolizumab? A Comprehensive Review - Mateusz Kciuk; Katarzyna Wanke; Weronika Kruczkowska; Beata Marciniak; Renata Kontek (Molecules)
The PD-1/PD-L1 pathway has emerged as a critical target in colorectal cancer (CRC) immunotherapy, with pembrolizumab, nivolumab, and dostarlimab demonstrating significant clinical efficacy, particularly in microsatellite instability-high (MSI-H) and mismatch repair-deficient (dMMR) tumors. However, a growing number of additional PD-1/PD-L1 inhibitors, including AMP-224, atezolizumab, avelumab, camrelizumab, durvalumab, envafolimab, sintilimab, spartalizumab, tislelizumab, and toripalimab, are currently under investigation, offering new possibilities for the expansion of treatment options. This review evaluates the therapeutic potential of these emerging agents, assessing their clinical development, mechanisms of action, and potential advantages over established therapies. Additionally, it explores key challenges such as primary and acquired resistance, limited efficacy in microsatellite-stable (MSS) CRC, and the complexities of combination strategies aimed at enhancing immunotherapeutic responses. By addressing these obstacles and highlighting prospects, this review provides insights into the evolving landscape of PD-1/PD-L1-targeted therapies in CRC and their potential to improve patient outcomes.